Multilocus Sequence Types and Antimicrobial Resistance of Campylobacter jejuni and C. coli Isolates of Human Patients From Beijing, China, 2017–2018 - Zhang, Penghang; Zhang, Xiaoai; Liu, Yuzhu; Jiang, Jinru; Shen, Zhangqi; Chen, Qian; Ma, Xiaochen (Frontiers in Microbiology, 2020)
Campylobacter species are zoonotic pathogens and the leading cause of bacterial enteritis worldwide. With the increase of antimicrobial resistance to fluoroquinolones and macrolides, they have been identified by the World Health Organization (WHO) as high-priority antimicrobial-resistant pathogens. There is currently little known about the prevalence and antimicrobial resistance characteristics of Campylobacter species in Beijing. In this study, we performed a 2-year surveillance of Campylobacter in Beijing, China. We used multilocus sequence typing (MLST) and antimicrobial susceptibility testing to analyze 236 Campylobacter isolates recovered from 230 clinical infectious cases in Beijing between 2017 and 2018. The Campylobacter isolation rate in diarrhea patients was 7.81%, with higher isolation rates in male patients than female patients and in autumn compared with other seasons. We identified 125 sequence types (STs) of 23 cloning complexes (CCs) among the 236 isolates, including four new alleles and 19 new STs. The most commonly isolated STs of Campylobacter jejuni were ST-22 and ST-760 (4.50%), and the most commonly isolated ST of Campylobacter coli was ST-9227 (16.67%). We also compared our isolates with clinical Campylobacter isolates from other countries in Asia, CC-353 of Campylobacter coli was found in eight countries, CC-1034 and CC-1287 of Campylobacter coli were found only in China. All C. jejuni isolates were resistant to at least one antimicrobial. C. jejuni showed the highest rate of resistance toward ciprofloxacin (94.50%), followed by tetracycline (93.50%), and nalidixic acid (92.00%), while C. coli showed highest resistance toward ciprofloxacin (94.44%) and tetracycline (94.44%) followed by nalidixic acid (88.89%). The most commonly observed MDR combination of C. jejuni were quinolone, phenicol and tetracycline (11.50%), while the most commonly observed MDR combination of C. coli were macrolide, quinolone, phenicol, tetracycline and lincosamide (30.56%). Surveillance of molecular characterization will provide important information for prevention of Campylobacter infection. This study enhances insight into Campylobacter infections in diarrheal patients, with relevance for treatment regimens in Beijing.